The Impact of Nurses in Disease Prevention and Health Promotion of Community People: Impact of Nurses in Disease Prevention and Health Promotion - Abdullah (NURSEARCHER (Journal of Nursing & Midwifery Sciences), 2026)
The role of nurses is not limited to clinical side only; they play a holistic role in health care setting in general and particularly in primary healthcare settings like early detection of diseases, patient health education, and health promotion. Nurses are the backbone and important pillar of primary healthcare settings, which play a crucial role in disease prevention in all area of health care setting, especially in chronic disease management. Public health nurses are involved closely with patients and they work directly with individuals and families as well as communities, as a result, early detection and intervention can improved health outcomes in communities. Nurses play a great role in community health setting when it is research base rational. According to WHO-2022, over 27 million nurses constitute approximately 59% of health professionals and serve as the bridge between healthcare systems and communities. So, the nurses must be involved as a major stake-holder in health care setting in Pakistan. In today’s world the non-communicable diseases (NCDs) emerging as the leading causes of worldwide morbidity and mortality. According to the World Health Organization (WHO), the percentage of NCDs for all types of mortality in the world is about 74%, with heart diseases, cancers, respiratory diseases, and diabetes representing the greatest burden. The health professionals, policy makers and expert know that the priority from curation is shift toward prevention and early detection and intervention, as growing evidence reveals that preventive strategies play significantly better health outcomes as compared to curation. According to the Global Status Report-2023 of World Health Organization on NCDs a critical implementation gap was identified that only 50% of member state have a multisectoral preventive policy for NCDs in their operational programs. It shows that how governments are serious in their primary health care in community level which is directly related to health inequities. This gap is clearly identified in COVID-19 pandemic that preventive services is so much important which was not present especially in rural areas and directly affect the health of community people. Government must strengthen the primary health care by upgrading the existing structure and create the position for community health nurses in Pakistan. Readiness and response to all type of disasters are key components of public health promotion and interventions. Public health Nurses are often the first responders to disasters and catastrophes, and they play a major role in keeping the public safe and healthy, during this type of situation. They can contribute in organizing medical care and give individuals care as well as basic necessities like food, drink, and shelter to needy people and lesson their health problems. Nurse-led preventive interventions and programs have a significant role in primary health care, but unfortunately in Pakistan it is not exist. Through these initiative health behaviors and preventive services utilization can be improved. Nurses can work and lead multidisciplinary teams in different health care setting and communities. Nurse-led initiatives reduce hospital admissions and improve chronic disease management especially in communities. The National Academy of Medicine (2023) in its report that "The Future of Nursing 2030" identifies "unleashing nurse-led prevention" as a serious priority, because the current healthcare systems is mostly rewarding the curative and treatment base services in term of money and no any incentive for preventive services. For attraction the preventive services must also be rewarded. In conclusion, it is imperative to move from theoretical potential of nursing in preventive medicine into measurable, scalable, and sustainable improvements in community health services through the leadership of nurses. Strengthening the Nurse-led preventive practices can enhance the health outcomes and reduce healthcare costs. For a successful heath care setting and sustainable improvement, it is suggested to contribute to a truly preventive, person-centered, and equitable healthcare systems in Pakistan.